2016
DOI: 10.1109/comst.2016.2537748
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of Smartphone Users Using Behavioral Biometrics

Abstract: Smartphones and tablets have become ubiquitous in our daily lives. Smartphones, in particular, have become more than personal assistants. These devices have provided new avenues for consumers to play, work and socialize whenever and wherever they want. Smartphones are small in size; so they are easy to handle and to stow and carry in users' pockets or purses. However, mobile devices are also susceptible to various problems. One of the greatest concerns is the possibility of breach in security and privacy if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(79 citation statements)
references
References 129 publications
0
79
0
Order By: Relevance
“…These concerns mainly originate from the fact that mobile devices (where information is stored) can be easily stolen and as a result access to confidential data can be compromised. In an attempt to come up against these security threats, many state-of-the-practice approaches involve authentication mechanisms such as passwords, unlock patterns, or even face or fingerprint recognition [2,3]. The use of these techniques, however, has been proved to be inefficient in some cases, firstly because they add overhead (thus users store passwords and pins), and secondly because they perform one-time authentication (if you are authenticated once, you get full access to the service/application functionality).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These concerns mainly originate from the fact that mobile devices (where information is stored) can be easily stolen and as a result access to confidential data can be compromised. In an attempt to come up against these security threats, many state-of-the-practice approaches involve authentication mechanisms such as passwords, unlock patterns, or even face or fingerprint recognition [2,3]. The use of these techniques, however, has been proved to be inefficient in some cases, firstly because they add overhead (thus users store passwords and pins), and secondly because they perform one-time authentication (if you are authenticated once, you get full access to the service/application functionality).…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to overcome the aforementioned issues, many research efforts are directed towards continuous implicit authentication on the basis of behavioral biometrics [2,5,6]. The main idea behind this approach is to take advantage of data that originate from the continuous interaction of the user with the mobile device, generate a number of features that uniquely model the user's interaction, and discriminate him/her among others [7,8].…”
Section: Resultsmentioning
confidence: 99%
“…An in-depth analysis of the evaluation results showed that the proposed scheme works effectively. (Alzubaidi and Kalita, 2016) provided a detailed review of seven different types of behavioral biometrics, including walking style, touchscreen interaction, signature, handwaving, keystroke dynamic, voice, and behavior sketching. (Yang et al, 2015) proposed OpenSesame, a scheme to authenticate users on the basis of handwaving patterns.…”
Section: Background and Related Workmentioning
confidence: 99%
“…To enhance the security of mobile devices and provide potential solutions to existing challenges in smartphone authentication, researchers have come up with numerous schemes, which perform authentication on the basis of behavioral biometrics (Alzubaidi and Kalita, 2016). These authentication schemes offer a way to continuously and passively authenticate different smartphone users by identifying their behavioral traits while interacting with smartphone.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the close connection between the existing masquerade attack detection approaches and the behavioral-based user verification solutions [8], these insider threats have been selected as the primary subject of study of the research presented in this paper. It is important to highlight that insider detection is inherently tied with the privacy concerns stated so far and, in turn, addresses the CIA (confidentiality, integrity, and availability) security principles.…”
Section: Introductionmentioning
confidence: 99%